The Role Of Talaga Bodas Tourist Destination Managers In Increasing Tourist Attractiveness - Abdurrahman, Salman Arif; Demolingo, Ramang H. (Jurnal Toursci, 2025)
This study aims to examine how managers play a role in developing and enhancing tourist attractions in Talaga Bodas, Garut Regency, West Java. Using a qualitative descriptive approach, data were collected through direct field observations, in-depth interviews, and document collection from managers, local residents, and tourists. The main finding is that the management role is still largely held by the Natural Resources Conservation Agency (BKSDA), while village governments and local communities are less involved. Currently, management focuses more on preserving and maintaining the area, but has not yet fully encompassed the development of tourist attractions, facility improvements, or integrated digital promotion. However, Talaga Bodas's extraordinary natural potential, community support, and tourist interest in nature and educational tourism offer significant opportunities for the development of this destination. Active involvement from managers is needed to build collaboration between the BKSDA, local government, and the community to create a sustainable destination management system. Strategic steps such as improving infrastructure, training human resources, and strengthening environmentally friendly digital promotion are crucial to attracting more tourists. This study demonstrates that the task of destination managers is not only to preserve nature but also to achieve a balance between economic, social, and ecological aspects. With collaborative management and a focus on community empowerment, Talaga Bodas has great potential to become a sustainable nature tourism destination, providing real benefits to local residents while enhancing the region's tourism reputation.